BOOK REVIEW: Martyn Rady, “Customary Law in Hungary: Courts, Texts and the Tripartitum”, Oxford, Oxford University Press, 2015, 266 p., ISBN: 9780198743910 - POP, Ioana-Terezia (Studia Universitatis Babeș-Bolyai Historia, 2017)
This new study authored by Martyn Rady brings a topical theme to our attention: common law in the Kingdom of Hungary. Due to the novelty of its approach, it is worthy of being signalled in Romanian historiography. The volume proposes a successful combination between elements of social and legal history. The author is a close friend of the Hungarian and Romanian scientific environment. Currently, he holds the position of professor at University College London, where he teaches History of Central Europe at the School of Slavonic and East European Studies. His research focuses on the area of the Kingdom of Hungary, and implicitly on Transylvania, whose destiny was tightly linked to Hungary until late in the Modern Age. Martyn Rady`s preoccupation for legal history also manifested by collaborating with Hungarian scholars on republishing the Kingdom of Hungary decrees (Decreta Regni Medievalis Hungariae). The last of this series, volume five, includes the bilingual (English and Latin) version of the Tripartitum. The time span which comprises the studies of the historian is a generous one. The lower limit is represented by the Middle Ages, and the upper one ends with the twentieth century. Analyzing the customary law (from the above-mentioned era), the work under scrutiny continues the author`s preoccupations for the customary and legal history of the Kingdom of Hungary. In Customary Law in Hungary: Courts, Texts and the Tripartitum the focus is upon the private, public, constitutional and procedural law in Hungary. The nature of the book is analytical and informative; by analyzing different sources, the author explains the interaction between written norms and their practical application, namely the function of this interaction in the case of Hungarian customs. The main source is the 16th century customary law code: The Tripartitum, written in 1514 by Ștefan Werbőczy (1458-1541). Other sources successfully used in a comparative way are as follows: attempts to codify the customary law posterior to the work of Werbőczy, as well as documents from the archives of Hungary and Romania.